What Are Teachers' and School Leaders' Major Concerns About New K-12 State Tests? Findings from the American Teacher and American School Leader Panels - Kaufman, Julia H. (RAND Corporation, 2015)
This report shares U.S. principals' and teachers' concerns about implementation of state assessment tests aligned to the new standards, drawing on new survey tools for understanding educators' perspectives: RAND's American Teacher Panel (ATP) and American School Leader Panel (ASLP). Findings indicate particular concern with students' test performance, as well as more prevalent concerns about the PARCC assessment compared with other assessments.